Antifungal prophylaxis with fluconazole in allogeneic stem cell transplantation recipients who had prior invasive aspergillosis with subsequent complete resolution by computed tomography. Issue 4 (3rd April 2018) - Akahoshi, Yu; Kimura, Shun-Ichi; Gomyo, Ayumi; Hayakawa, Jin; Tamaki, Masaharu; Harada, Naonori; Kusuda, Machiko; Kameda, Kazuaki; Ugai, Tomotaka; Wada, Hidenori; Ishihara, Yuko; Kawamura, Koji; et al.
Abstract: Background: Consensus has yet to be reached regarding secondary prophylaxis in allogeneic hematopoietic stem cell transplantation (HSCT) with a complete resolution of invasive aspergillosis (IA) confirmed by chest computed tomography (CT). Methods: We retrospectively evaluated the feasibility of antifungal prophylaxis with fluconazole in allogeneic HSCT recipients who had previously developed IA which showed complete resolution as confirmed by chest CT before HSCT. Consecutive adult patients who underwent allogeneic HSCT at our institution and who had received fluconazole as systemic antifungal prophylaxis from June 2007 to January 2015 were included. We compared the clinical outcomes between patients with a past history of IA who showed a complete resolution of chest CT abnormalities ( n = 13) and those without a previous history of IA ( n = 137). Results: The cumulative incidence of proven or probable IA was 8.8% in the group without a past history of IA and 0.0% in the group with a past history of IA ( p = .268). The cumulative incidence of proven or probable invasive fungal disease (IFD) within 100 days after allogeneic HSCT was 10.9% in the group without a past history of IA and 15.4% in the group with a past history of IA ( p = .647). Fluconazole was switched to anti-mould agents in two-thirds of the patients in each group by day 100 after HSCT. Conclusions: Fluconazole was confirmed to be an acceptable prophylactic agent early after allogeneic HSCT in appropriately selected patients.